Hybrid N-Type Poly-Si Ultra-Thin Nanowire Shell Channel with P-Substrate Structure by Electron Beam Lithography Adjustment for Junctionless Field-Effect Transistors. (1st January 2018) - Tsai, Meng-Ju; Chiang, Ya-Ying; Lin, Yu-Ru; Kurniawan, Erry Dwi; Wu, Yung-Chun
Abstract : This study proposes a new hybrid N channel/P substrate for junctionless field-effect transistors (JL-FET) by using electron beam lithography adjustment for the shell structure. The nanowire (NW) shell JL-FET exhibits the superior electrical properties, including high ON/OFF current ratio of 6 × 10 6, low subthreshold swing (SS) of 95 mV/decade and drain-induced barrier lowering value (DIBL) of 50 mV/V. This NW shell structure JL-FET is simple to fabricate, and highly favorable for use in advanced System-on-panel (SoP) and three-dimensional (3-D) stacked IC applications.